Strategi Badan Pendapatan Daerah (BAPENDA) Kota Denpasar Dalam Meningkatkan Kepatuhan Dan Kesadaran Wajib Pajak PBB P2 - Ariningsih, Ni Made; Prabawati, Ni Putu Anik; Veratiani, Gek Aris (Lenggogeni Data Publishing, 2025)
The Regional Revenue Agency (BAPENDA) of Denpasar City plays a significant role in managing and optimizing regional revenue. The main purpose of this research is to analyze the strategies implemented by BAPENDA Denpasar City in improving taxpayers’ compliance and awareness of Urban and Rural Land and Building Tax (PBB-P2). This study employs a qualitative method with a descriptive approach, using data collection techniques through documentation, observation, and interviews. The analysis is based on the Strategic Management Theory proposed by Wheelen and Hunger, which includes several indicators: (1) Environmental Analysis, (2) Strategy Formulation, (3) Strategy Implementation, and (4) Evaluation and Control. The results indicate that BAPENDA’s strategies to enhance taxpayers’ compliance and awareness of PBB-P2, when viewed through the indicators of Environmental Analysis, Strategy Formulation, and Evaluation and Control, have not been optimally implemented. This condition is caused by unutilized opportunities and strengths, as well as threats and weaknesses that have not been adequately addressed. Meanwhile, the SWOT analysis by Freddy Rangkuti (Strengths, Weaknesses, Opportunities, and Threats) produces several strategic recommendations, including: (1) enhancing and expanding administrative service features on the PAGI Denpasar application and mobile service units; (2) developing a reliable and integrated system to assist BAPENDA in monitoring land and building ownership data; (3) conducting PBB-P2 tax education through social media and establishing information booths at public events such as Denfest; and (4) actively organizing training programs or workshops while strengthening coordination among divisions and across sectors with community leaders (kaling/kadus). Abstrak BAPENDA Kota Denpasar berperan didalam pengelolaan dan mengoptimalkan penerimaan daerah. Tujuan pokok dari penelitian ini untuk menganalisa mengenai strategi yang dijalankan BAPENDA Kota Denpasar dalam meningkatkan kepatuhan dan kesadaran wajib pajak PBB P2. Metode penelitian yang digunakan kualitatif, pendekatan deskriptif dengan teknik pengumpulan data melalui dokumentasi, observasi, dan wawancara. Teori yang digunakan menganalisa yaitu teori Manajemen Strategi berdasarkan teori Wheelen dan Hunger adapun beberapa indikatornya yang meliputi (1) Analisa Lingkungan, (2) Formulasi Strategi, (3) Implementasi Strategi, (4) Evaluasi dan Pengendalian. Hasil penelitian bahwasanya strategi peningkatan kepatuhan dan kesadaran wajib pajak PBB P2 yang dilakukan BAPENDA dilihat pada indikator Analisa Lingkungan, Formulasi Strategi, serta Evaluasi dan Pengendalian belum terlaksana secara optimal. Hal tersebut disebabkan peluang dan kekuatan belum termanfaatkan, kemudian ancaman dan kelemahan belum tertangani secara maksimal dan menyeluruh. Sementara itu analisa SWOT dari Freddy Rangkuti (Strengths, Weakness, Opportunities, and Threats) menghasilkan rumusan strategi dengan kegiatan diantaranya: (1) peningkatan dan memperluas fitur-fitur layanan administrasi pada aplikasi PAGI Denpasar dan layanan Mobil Keliling, (2) pembuatan sistem handal yang terintegrasi yang membantu BAPENDA memantau data kepemilikan objek PBB, (3) edukasi pajak PBB P2 memanfaatkan media social dan membuat booth layanan informasi di event-event seperti Denfest, (4) aktif mengadakan pelatihan ataupun bimtek dan menguatkan koordinasi antar bidang dan lintas sektor kaling/kadus. Kata Kunci: Kepetuhan dan Kesadaran Wajib Pajak, PBB P2, SWOT, Manajemen Strategi